POLICY BACKLASH AGAINST EQUALITY REFORMS: A MULTI-LEVEL REVIEW OF THREAT, MORALIZATION, AND MOBILIZATION - Yunilisiah; Aditia, Rafinita; Hutapia (International Journal Multidisciplinary (IJMI), 2026)
Objective: Equality-oriented policy reforms addressing gender, disability, race, and social inclusion have expanded globally, yet their implementation is frequently accompanied by persistent and organized resistance. This tension raises a critical question about why formally adopted equality policies often struggle to achieve long-term sustainability. This study aims to explain how backlash against equality reforms emerges, stabilizes, and constrains policy trajectories over time. Method: Using a qualitative research design based on secondary data, the study conducts an analytical review and qualitative evidence synthesis of scholarly literature, policy documents, and institutional analyses. Through systematic document analysis and thematic synthesis, the research integrates findings across policy sectors and contexts to identify recurring mechanisms shaping backlash dynamics.Result: The study demonstrates that backlash operates through a multi-level process linking perceived threats to status, identity, and social order; the moralization of policy debates that legitimizes opposition; and political mobilization that institutionalizes resistance within governance structures. These mechanisms interact dynamically, transforming individual anxieties into moral claims and sustained collective action, thereby embedding resistance within policy processes rather than limiting it to episodic dissent.Novelty: The originality of this study lies in its integrative framework, which connects psychological, discursive, and institutional dimensions of backlash into a coherent explanatory model. Theoretically, it advances understanding of backlash as a structured and self-reinforcing political process. Practically, it offers analytical insights relevant to the design and implementation of equality policies that are more resilient to organized resistance.